2018
DOI: 10.1021/acssuschemeng.8b02406
|View full text |Cite
|
Sign up to set email alerts
|

Compact TiO2/Anatase TiO2 Single-Crystalline Nanoparticle Electron-Transport Bilayer for Efficient Planar Perovskite Solar Cells

Abstract: Electron-transport layer (ETL)/perovskite interface modification plays a key task for producing efficient planar perovskite solar cells (PSCs). In this study, interfacial modification of compact TiO2 using novel, one-step hydrothermally synthesized single-crystalline anatase (AT) titania nanoparticles (TiO2 NPs) (average diameter = 6–10 nm) was applied as an ETL bilayer to enhance the efficient charge generation and extraction and eliminate the electron–hole recombination ratio. We report here an easy approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 70 publications
0
33
0
Order By: Relevance
“…Furthermore, TiO 2 can produce a smooth film surface to improve charge transfer while maintaining the uniformity [19,23]. Several deposition methods, such as spin-coating, spray pyrolysis deposition (SPD), atomic layer deposition (ALD), chemical vapor deposition (CVD), sputtering, have been used to prepare TiO 2 compact layer (CL) [18,19,23,[26][27][28][29][30]. The current work investigates the preparation of high-quality (compact, uniform, and reproducible) TiO 2 films by the SPD technique so that the film can be used as an ETL for the fabrication of efficient PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, TiO 2 can produce a smooth film surface to improve charge transfer while maintaining the uniformity [19,23]. Several deposition methods, such as spin-coating, spray pyrolysis deposition (SPD), atomic layer deposition (ALD), chemical vapor deposition (CVD), sputtering, have been used to prepare TiO 2 compact layer (CL) [18,19,23,[26][27][28][29][30]. The current work investigates the preparation of high-quality (compact, uniform, and reproducible) TiO 2 films by the SPD technique so that the film can be used as an ETL for the fabrication of efficient PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…High-quality mesoporous TiO 2 scaffold films and TiO 2 CL require a high-temperature sintering (> 450 °C) step, which limits their applications in future flexible PSCs and solar modules. The active surface area and performance of the devices was improved by forming the perovskite layer on a layer composed of TiO 2 CL/TiO 2 nanoparticles [ 16 , 17 , 18 ]. The development of PHJ PSCs with low-temperature processed (< 150 °C) ETL CLs has attracted significant attention for their simple device framework [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…This quenching phenomenon indicated that the charge separation process is effectively occurred by the electron transfer from the conduction band of CdS to the conduction band of TiO 2 with low recombination rate. 33,35,36 Figure 2 shows XRD patterns of the TiO 2 nanoparticles without and with CdS QDs (2%, 6%, and 10%). The characteristic peak positions at 25.3 (101), 37.6 (004), 47.9 (200), 54.7 (105), 62.7 (204), and 75.1 (215) appeared in all samples, corresponding to the anatase-TiO 2 phase.…”
Section: Resultsmentioning
confidence: 99%